The Mackenzie Inuit Whale Bone Industry: Raw Material, Tool Manufacture, Scheduling, and Trade - Betts, Matthew W. (ARCTIC, 2009)
The bones of bowhead whales (Balaena mysticetus) were used by Mackenzie Inuit groups in producing a number of items essential to transportation and procurement. However, the whale bone industry, and its relationship to Mackenzie Inuit economic and social systems, is poorly understood. A recently excavated archaeological assemblage from McKinley Bay, Northwest Territories, provides a record of intensive Nuvugarmiut whale bone tool manufacture, which can be used to reconstruct a reduction sequence. Bowhead bone reduction at McKinley Bay focused on ribs, which were transversely worked into large sections. Cortical blanks were isolated from central rib sections, but proximal and distal rib sections were treated directly as blanks and preforms for the production of large durable tools, such as harpoon heads, adze sockets, mattock blades, and picks. The intensive whale bone reduction at McKinley Bay was part of a broader gearing-up strategy focused on the manufacture and repair of sleds and harpoons needed for the late winter migration and spring seal hunt. More generally, because the whale bone industry was intimately related to the bowhead hunt and its proceeds, it may provide fundamental insights about key aspects of coastal whaling societies, such as social organization, redistribution, and inter-territorial trade. Les groupes d’Inuits du Mackenzie se servaient des os de baleines boréales (Balaena mysticetus) pour produire un certain nombre d’articles essentiels en matière de transport et d’approvisionnement. Cependant, l’industrie des os de baleine, de même que son lien avec les systèmes socioéconomiques des Inuits du Mackenzie, sont mal compris. Grâce à des fouilles archéologiques récentes à la baie de McKinley, dans les Territoires du Nord-Ouest, on a découvert une installation de fabrication intensive d’outils en os de baleine au Nuvugarmiut, ce qui a permis de reconstruire une séquence de transformation. La transformation d’os de baleines boréales à la baie de McKinley portait sur les côtes de baleine. ...